APPLICATION OF WATERFALL MODEL ON PUBLIC SERVICE INFORMATION SYSTEM WITH WEBSITE BASED IN TUNGKARAN VILLAGE - Sofyar Sofyar; Muhammad Rafi'i; Sunni Risdayati; Muhammad Fajrian Noor; Syarifil Anwar; Isdamayanti Isdamayanti (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
The research was conducted in Tungkaran Village, Banjar Regency, to improve the efficiency and quality of public services provided to the residents. The system manages various community services, including issuing tailored certificates such as Certificate of Incapacity (SK Not Incapacitated), Death Certificate (SK Death), Certificate of Moving (SK Moving), Certificate of Business (SKU), and Certificate of Domicile (SK Domicile). The Community Service Data Information System in Tungkaran Village provides significant benefits in letter writing services and streamlines processes for the community. The adoption of this technology is expected to enhance community satisfaction.